THE INFLUENCE OF LOGISTICS OVER THE OCCURRENCE OF SPATIAL AGGLOMERATION OF BUSINESSES - MĂDĂLINA S. MATICIUC; ALEXANDRU CONSTANTIN PETRACHE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
This paper involves an examination of the literature that refers to the various methods of spatial agglomeration of businesses where the focus is actually minimizing transportation costs. The research has a predominantly theoretical nature, based on exploratory method, being focused on the literature review to highlight the evolution of different forms of spatial organization so we can identify the advantages of acquiring further knowledge needed to the applied research, providing in this manner prospects for progress. The vicinity of the representatives of the economic, political and educational environment presents many advantages with regard to reciprocal relationships that can develop within these, whether formal or informal, highlighting the potential of flexible innovative forms of spatial organization of clusters. Spatial agglomeration theories that were developed in the course of time, is a cornerstone for new innovative forms of business spatial organization such as clusters and networks of clusters that are offering many advantages in terms of cost of transportation. The evolution of business spatial agglomerations shows that the vast majority of companies aim to ensure competitive advantage not only in close locations to increase the generation of innovation and reduced transport costs, but also through access to knowledge in a fast and easy way. The work comes in support of these ideas , proposing in the conclusions part a new model of business agglomeration which does not require physical proximity but one of cloud type.